Inadequate Communication Exacerbates the Support Needs of Current and Bereaved Caregivers in Advanced Heart Failure and Impedes Shared Decision-making. Issue 1 (January 2019) - Fitzsimons, Donna; Doherty, Leanne C.; Murphy, Mary; Dixon, Lana; Donnelly, Patrick; McDonald, Kenneth; McIlfatrick, Sonja
Abstract : Background: Clinicians face considerable challenges in identifying patients with advanced heart failure who experience significant symptom burden at the end of life. Often, these patients are cared for in the community by a loved one who has limited access to support from specialist services, including palliative care. Aim: The aims of this study were to explore caregivers' experience when caring for a loved one with advanced heart failure at the end of life and to identify any unmet psychosocial needs. Methods: This article reports findings of a qualitative study, using semistructured, one-to-one interviews with current and bereaved caregivers, who participated in a larger mixed-methods study. Interviews were conducted by a trained researcher, digitally recorded, transcribed verbatim, and imported to NVivo 11 for data management and coding. Data were analyzed using thematic analysis and an inductive approach. Results: The 30 interviews included 20 current caregivers and 10 bereaved caregivers. The central feature of the caregivers' experience was identified as being "a physical and emotional rollercoaster." There were 3 main themes identified: poor communication, living with uncertainty, and lack of service provision. These themes were supported by 6 subthemes: inadequate understanding of palliative care, a 24/7 physical burden, emotional burden, inability to plan, no care continuity, and dying lonely and unsupported. Conclusions: Caregivers in advanced heart failure need clearer communication regarding diagnosis and prognosis of their loved one's condition to help with the uncertainty of their situation. Improved identification of palliative care needs and more coordinated service provision are urgently required to address their physical and emotional challenges from diagnosis through bereavement. Abstract : Supplemental digital content is available in the text.